CT‐determined pulmonary artery to aorta ratio as a predictor of elevated pulmonary artery pressure and survival in idiopathic pulmonary fibrosis. Issue 7 (10th May 2017) - Yagi, Mitsuaki; Taniguchi, Hiroyuki; Kondoh, Yasuhiro; Ando, Masahiko; Kimura, Tomoki; Kataoka, Kensuke; Furukawa, Taiki; Suzuki, Atsushi; Johkoh, Takeshi; Hasegawa, Yoshinori
ABSTRACT: Background and objective: Elevated mean pulmonary artery pressure (mPAP) is a significant prognostic indicator in idiopathic pulmonary fibrosis (IPF). It has been reported that the computed tomography‐determined ratio of the diameter of the pulmonary artery to the aorta (PA:A) is correlated with mPAP in various respiratory diseases. However, in patients with IPF, whether the PA:A can be used to predict elevated mPAP and the prognostic value of the PA:A has not been fully evaluated. Methods: We conducted a single‐centre, observational study of 177 consecutive IPF patients who underwent right heart catheterization. We examined the association between the PA:A and mPAP in these patients, and performed a receiver operating characteristic (ROC) analysis to test the diagnostic accuracy of the PA:A in predicting mPAP > 20 mm Hg (pulmonary hypertension (PH) or borderline PH) in relation to survival. Results: In a multivariate linear regression analysis, the PA:A, 6‐min walk distance and diffusion capacity for carbon monoxide (DLCO ) % predicted were independent explanatory variables of elevated mPAP ( P  < 0.0001, P  = 0.009 and P  = 0.002, respectively). ROC analysis revealed a PA:A > 0.9 to be optimal for predicting mPAP > 20 mmHg (area under the curve (AUC) = 0.75; 95% CI: 0.65–0.84). Patients with a PA:A > 0.9 also had a worse prognosis ( P  = 0.009). Conclusion: Measurement of the PA:A is a useful and convenient method to predict elevated mPAP in IPF at initial evaluation. Moreover, a PA:A >0.9 was found to be an indicator of worse prognosis. Abstract : In idiopathic pulmonary fibrosis (IPF), the ratio of the diameter of the pulmonary artery to the aorta (PA:A) was significantly correlated with mean pulmonary artery pressure (mPAP). In multivariate analysis, the PA:A, 6‐min walk distance (6MWD) and diffusion capacity for carbon monoxide (DLCO ) % predicted were independent predictors of mPAP. Moreover, a PA:A > 0.9 was associated with a worse prognosis.